The role of informal learning activities in improving L2 lexical access and acquisition in L1 Arabic speakers learning EFL. Issue 5 (20th October 2018) - Masrai, Ahmed; Milton, James
ABSTRACT: Case studies in lexical uptake suggest that some well reported language learning strategies, such as extensive reading and listening to songs, can be quantified accurately in terms of time spent on task and the nature of the vocabulary input they provide. These studies also show that these strategies can link very convincingly to growth in vocabulary size. This study adopts this approach in a case study which investigates the impact of extensive reading on the speed of lexical access and uptake from written sources. The study is conducted with a native speaker of Arabic learning English and previous studies have suggested that learners from this background are slow in adopting efficient reading processes for use in English, and that this may result from limited time spent in reading in any language. The participant in this study spent nearly 50 hours watching English language films and news reports with subtitles. Measures of vocabulary uptake suggest he added nearly 900 words to the orthographic side of his lexicon from this source through the intervention, and his reading speed increased by over 30%. It is suggested, therefore, that an extensive reading strategy can make quantifiable differences to a learner's vocabulary uptake and reading speed.